Gender-Dependent Reference Range of Serum Calcitonin Levels in Healthy Korean Adults - Song, Eyun (Endocrinol Metab (Seoul), 2021)
BACKGROUND: Serum calcitonin measurement contains various clinical and methodological aspects. Its reference level is wide and unclear despite sensitive calcitonin kits are available. This study aimed to identify the specific reference range in the healthy Korean adults. METHODS: Subjects were ≥20 years with available calcitonin (measured by a two-site immunoradiometric assay) data by a routine health checkup. Three groups were defined as all eligible subjects (group 1, n=10,566); subjects without self or family history of thyroid disease (group 2, n=5,152); and subjects without chronic kidney disease, autoimmune thyroid disease, medication of proton pump inhibitor/H2 blocker/steroid, or other malignancies (group 3, n=4,638). RESULTS: This study included 6,341 male and 4,225 female subjects. Males had higher mean calcitonin than females (2.3 pg/mL vs. 1.9 pg/mL, P<0.001) in group 1. This gender difference remained similar in groups 2 and 3. Calcitonin according to age or body mass index was not significant in both genders. Higher calcitonin in smoking than nonsmoking men was observed but not in women. Sixty-nine subjects had calcitonin higher than the upper reference limit (10 pg/mL) and 64 of them had factors associated with hypercalcitoninemia besides medullary thyroid cancer. Our study suggests the reference intervals for men who were non, ex-, current smokers, and women (irrespective of smoking status) as <5.7, <7.1, <7.9, and <3.6 pg/mL, respectively. CONCLUSION: Specific calcitonin reference range should be provided considering for sex and smoking status. Taking account for several factors known to induce hypercalcitoninemia can help interpret the gray zone of moderately elevated calcitonin.